Model predictive control for Active-Bridge-Active-Clamp (ABAC) converter - Chen, Ling; Tarisciotti, Luca; Costabeber, Alessando; Gottardo, Davide; Zanchetta, Pericle; Wheeler, Patrick (2018)
The Dual-Active-Bridge is a well-established isolated, bidirectional DC/DC topology suitable for applications where high efficiency, galvanic isolation and large voltage conversion ratios are required. However, in low voltage high power cases, the output current ripple is significant and large filtering capacitance is needed. As an alternative to the standard Dual-Active-Bridge, the Active-Bridge-Active- Clamp (ABAC) converter is presented in this paper. The ABAC converter overcomes the current ripple limitation of Dual Active Bridge by presenting a current interleaved structure. An average switching model is developed for the ABAC converter by neglecting the dynamic on the high frequency link, and a Model Predictive Control (MPC) is proposed. The control features a reduced prediction horizon and a fixed switching frequency. Finally, simulation results for a 10kW ABAC converter are provided to validate the theoretical claims.